Special Functions of Hypercomplex Variable on the Lattice Based on SU(1,1) - Faustino, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
Based on the representation of a set of canonical operators on the lattice hZn, which are Clifford-vector-valued, we will introduce new families of special functions of hypercomplex variable possessing su(1,1) symmetries.